Role of calcium carbonate on hardness and fracture toughness of carbon fiber reinforced epoxy composites. (2021) - Suresha, B.; Hemanth, G.; Rakesh, Apurva; Adarsh, K.M.
Abstract: The present study seeks the role of nano-calcium carbonate (n-CC) on physical properties and fracture toughness of unidirectional carbon fiber/epoxy (UDCF/Ep) composites. The loading of n-CC is 1.5 wt. %, 3 wt. % and 5 wt. % in UDCF/Ep composite. Unfilled and n-CC filled UDCF/Ep composites were probed for the density, hardness, and single edge notched bending (SENB) test in accordance with governing ASTM standards. The measured density and hardness of the composites augmented with n-CC loading. However, n-CC was found to enhance the fracture toughness until 3 wt. % filler. Post-test, specimens were examined under a scanning electron microscope to analyze the involved fracture features. The SENB specimen was modeled and analyzed in the ANSYS for the peak load condition which affirmed the region of maximum stress intensity.